Experiencing Change: Rhythms of Everyday Life Between Continuities and Disruptions - Awad, Sarah H. (Qualitative Studies, 2021)
Change is a constant condition of everyday life that we experience and transition through while often maintaining a sense of stability and continuity. But inevitably we come across disruptive changes that call into question the meanings we take for granted and thereby rupture life as we know it. How do those changes affect our rhythms of living? How do we make meaning of the changes and subsequently act upon them? How do individual, social, and environmental changes reciprocally influence one another? These are the guiding questions of this paper. The questions are explored by means of a sociocultural psychological approach to ruptures in the life-course coupled with Lefebvre’s rhythmanalysis. It is argued that those questions can be investigated within five interrelated analytical domains; time, space, the body, social others, and symbolic resources. Rather than primarily emphasizing adaptation to change, the analytical framework’s key focus is meaning-making, looking at how we integrate or resist new rhythms in our lives.